Exchange Volatility and Monetary Policy to Maintain Economic Stability - Misrah; Faujiah, Nurul; Royzak, Abdul (Tawazuna, 2023)
One of the indicators that affects the direction of economic growth in various countries is volatility. Volatility can influence the stability of economic conditions both within the commercial and financial sectors, with each country implementing it differently. This article discusses exchange rate volatility and monetary policy in order to maintain economic stability. The authors used library research for this article. According to the various study references, monetary policy has an impact on the rate of economic growth, which can be accomplished by increasing volatility with the goal of stabilizing a country's economy.